Anomalous/Paranormal Experiences reported by nurses themselves and in relation with theirs patients in Hospitals - Parra, Alejandro; Gimenez Amarilla, Paola (Journal of Scientific Exploration, 2017)
Existing reports of Anomalous/Paranormal Experiences (APE) by nurses in the hospital/Health centers settings. The aim of this research project is carry out of descriptive analysis and quantitative/qualitative study of near-death and out of body experience, sense of "presence", an apparition, floating lights, luminescence, or unexplained object movements, hearing strange noises, voices or dialogues, crying or moaning, seeing energy fields, lights or "electric shock" around an inpatient have had an extrasensory experience, malfunction of equipment or medical intrumental in certain patients, and/or spiritual/paranormal form of intervention. The structure of the nursing study closely follow concurrent research taking place with three of 8 hospitals. The main aim are to determine the extent of occurrence of certain types of APEs in hospitals and their relationship to job stress and psychological absorption, to assess the frequency of certain unusual APEs in hospital, to assess the level of psychological absorption of people experiencing these perceptions, and to compare experiences nurses without experience in their degree of job stress and absorption. The recruited sample (up to December 20th.) consisted of 39 nurses (Experiencers) who reported paranormal experiences in hospitals and 61 nurses as control group (Non-experiencers). All of them filled four instruments: The Anomalous/Paranormal Experiences in Nurse & Health Workers (which measures frequency of paranormal/anomalous experiencies), the Maslach Burnout Inventory which leading measure of burnout, the Hallucinations Experiences Questionnaire, and Tellegen Absorption Scale and an open, non-structured interview based on questions of the first instrument. Non parametric statistics was used to test the hypotheses, and the analysis were transformed into a zs (one-tailed). The results showed that nurses reporting these experiences tended to experience greater job stress is not confirmed, however, nurses who reported a combination of perceptual experiences and psychological absorption (high level), tended to score higher work stress compared to those who do not report such experiences. Nurses reporting these experiences tended to report greater psychological absorption, and also tended to report greater proneness to hallucinate. The best predictor was psychological absorption in nurses with APE experiences [β = 0.33, df = 3, p = 0.005; R2 = 0.12] compared to the group nurses no-experiencers.